PERENCANAAN DINDING PENAHAN TANAH SHEET PILE DENGA PERKUATAN GROUND ANCHOR PADA RUMAH SAKIT BHAKTI BUNDA KOTA MALANG - Pramesthi, Shifa Ardhelia; Suryo, Eko Andi; ., Harimurti (Jurnal Mahasiswa Jurusan Teknik Sipil, 2020)
Bhakti Bunda Hospital Malang City reconstructed the building structure so that a stronger retaining wall structure was needed. By using the GeoSlope program and based on the soil parameter data obtained, the results of the calculation of the value of the safety factor for slope stability which are given a building load of 26.9kN/m2 as the load of the Bhakti Bunda Hospital with results between 0.879 – 1.000 with various types of analysis. This indicates that landslides will occur on the slopes of the hospital so that a slope reinforcement structure is needed. In this study, the retaining wall reinforcement used a sheet pile Cold Formed Combi Wall MMHZ I 1180C and using 7 strands with a diameter of 0.52 inches with the type of tendon A 416 / A416M-06 Grade 27 for the anchor. Then for the calculation of the Ground Anchor, the  installation of the anchor are 8 meters as a fixed length and 11 meters as a free length and with a ground anchor diameter of 0,15 m can withstand lateral ground pressure and lateral loads imposed on the ground. The safety factor value was obtained in the analysis calculation of 2,282 for the sliding stability and 3,454 for the over turning stability. Then modeling the PLAXIS 2D V20 program and obtained a safety factor of 2,068 which states that the sheet pile and ground anchor design are safe. Keywords: Retaining Wall, Sheet Pile, Ground Anchor, Safety Factor.